Overview Of Enabling Works For Waterfront Structures – Design & Construction - Raja Rajan. K; Nagarajan. D; Vijayakumar. T (Deep Foundations Institute, 2022)
Major bridges crossing mighty rivers must be constructed in flowing water. Constructing the sub-structure in water has been a challenging job for contractor. Special construction techniques with marine fleets to be adopted for waterfront construction. Enabling works like temporary piling platform and cofferdam used for pile and pile cap construction. Apart from this, enabling works like load out jetty to transport the materials from land to water; temporary walkway for access of workman to work location; temporary access bridge for construction vehicles movement; temporary liners for tower crane foundation; Concrete block to act as dead man anchor for barge movements were all required by the contractor for smooth functioning of site as per construction schedule. Investment in enabling works by contractor plays a significant role on profit margin of the project and of course with utmost safety. Design of enabling works for waterfront structures involves hydrological data like afflux, bathymetry survey, current force, scour depth and wave force to be taken cautiously for safe and economic design. Type of foundation and pile/well cap top level corresponding to water levels shall influence the construction scheme. Usage of geotechnical software like Wallap and Plaxis required for enabling work design to enhance the safety of the structure. Bathymetry and soil condition play a critical role in design and construction of enabling works. Water Discharge quantity in river along with water levels like low water level, high flood level, seasonal fluctuation of water levels has a great impact on design of enabling works. Establishing enabling works for waterfront construction near to an existing bridge is an additional challenge for the contractor. Along with design, constructing the enabling works in water requires special construction methodology and sequence of work. This paper shall provide insights on overview of design and construction of enabling works for waterfront construction.